Integrative transcriptome and phenome analysis reveals unique regulatory cascades controlling the intraerythrocytic asexual and sexual development of human malaria parasites - Birkholtz, Lyn-Marie (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2019.